Safe and Resilient Infrastructure in the Philippines : Applications of International Experience - World Bank Group (Washington, DC, 2015)
The report presents the results of a detailed vulnerability assessment and summarizes the prioritization methodology developed to guide investment decisions on the strengthening of critical assets in Metropolitan Manila. With support from the World Bank, the engagement on Safe and Resilient Infrastructure has carried out a preliminary structural assessment of over seven hundred public school campuses and twenty hospitals retained by the Department of Health in Metro Manila. The report also highlights the lessons learned from seismic retrofitting programs implemented throughout the world, as showcased during the Forum on Safe and Resilient Infrastructure that took place in Manila, Philippines, in October 2013. This report is divided into three sections. First, it establishes the technical principles of earthquake risk management. Second, it details the experience of the Philippines to date in developing an integrated earthquake risk management program, focusing on the methodology and results of a vulnerability assessment and prioritization conducted under the Safe and Resilient Infrastructure Program. Last, it reviews international experience with earthquake risk management programs of various scales and scopes, through the cases of California, Romania, Turkey, and Indonesia. The key messages of the report are as follows: An integrated approach to earthquake risk management can strengthen key buildings and infrastructure and reduce the damaging effects of future disasters in the Philippines. Earthquake risk management and strengthening programs initiated by both the public and private sectors in many countries often consist of three phases: risk audit, risk assessment, and implementation. Several key technical components must be considered in the design of a phased earthquake risk management program, including a prioritization methodology.